The Impact of Smoking on Subgingival Plaque and the Development of Periodontitis: A Literature Review - Zhang, Jiaxin; Yu, Jialu; Dou, Jinge; Hu, Pingyue; Guo, Qiang (Frontiers in Oral Health, 2021)
Smoking seriously affects oral health and causes a variety of oral diseases. Numerous clinical data show that smoking significantly increases the risk of periodontitis, and the duration and amount of smoking are positively correlated with the severity of periodontitis. In fact, smoking creates an environment conducive to the colonization of periodontopathogens, which affects the process of periodontitis. Since subgingival plaque which harbors periodontopathogens is the initiation factor of periodontitis, it is critical to study the impact of smoking on subgingival microbiota for understanding the relationship between smoking and periodontitis. Continuous advances have been made on the effects of smoking on subgingival plaque and the development of periodontitis. Smoking is observed to enhance the pathogenicity of periodontopathogens, especially the red complex microorganisms, via promoting their colonization and infection, and regulating the expression and function of multiple virulence factors. Furthermore, smoking has a negative impact on periodontal microecological homeostasis, which is reflected in the decrease of commensal bacteria and the increase of periodontopathogens, as well as the changes in the interaction between periodontopathogens and their commensal microbes in subgingival biofilm, thus influencing the pathogenicity of the subgingival plaque. In summary, the mechanism of smoking on subgingival plaque microorganisms represented by the red complex and its effect on the periodontal microecology still need to be further explored. The relevant research results are of great significance for guiding the periodontal clinical treatment of smoking population. This review summarizes the effects and relevant mechanisms of smoking on subgingival plaque and the development of periodontitis.